Didactic Syntax Proposal to Primary Education’s future teachers - Davis González, Ana (Didáctica. Lengua y Literatura, 2022)
The following paper is a CIMA’s application (Classroom Improvement Cycle) carried out in the Spanish Language and its Didactics subject (Primary Education Degree, University of Seville). It consists of a didactic proposal on the teaching of syntactic analysis in the university education of future primary school teachers. The starting hypothesis is the distance between the overcoming of the traditional syntax by academic research, and its persistence in pre-university education. Our opinion is that, for the syntactic analysis’ teaching to be effective, it should begin to progressively break with such a gap in the Primary Education Degree, modifying some issues of traditional syntactic analysis in Education (for instance, including semantics or working with contextualized and not isolated sentences). Such has been the CIMA’s objective that we present in the following pages.